Theoretical and Experimental Study of Lubricant Influence on Performance of Refrigeration Compressors - 杨传波; 张薇; 郭漪; 李连生 (Zhileng xuebao)
A reasonable mathematical model describing the working processes of scroll compressors was presented to analyze the influence of lubricating oil content on compressors performance. The relation curves of oil content to the volumetric efficiency, input power, discharge temperature, refrigerating output, and COP were obtained. Moreover, to verify the computing results,experiments under the conditions of various speeds, various oil contents, and various working conditions were performed at a test rig for automobile scroll compressors. The results show that the best oil content is 7%-9%.